A Different Light on Normalization: Critical Theory and Responsive Evaluation Studying Social Justice in Participation Practices. Issue 146 (June 2015) - Woelders, Susan; Abma, Tineke
Abstract: Responsive evaluation provides guidelines to include various stakeholders in dialogue. However, a substantial theory to understand power asymmetries and inequalities is lacking. The purpose of this article is to consider which theoretical framework for societal critique can be helpful to evaluate practices in relation to social justice. These questions will be addressed using fragments from a responsive evaluation study on the involvement of people with an intellectual disability in public policy. Our study shows that Foucault's framework on normalization was helpful. It revealed that the engagement and striving for equality and social justice can turn out to be disciplining itself.